Study of the potential suitability of chrysanthemum plant areas with the suitability matrix overlay method - Ramadhoni, Muhammad Syarifuddin Nur; Sumitra, Moch. Kahfi Tri Agfria; Mahetsa, Ranu Yolan Eky (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Chrysanthemums are ornamental and floricultural plants that have an important role in Indonesia because they are used for religious ceremonies, decorations, and even health therapy. Today, chrysanthemums are considered a trendsetter in the cut flower industry in Indonesia because of their advantages: rich in color, size, and shape, durable, and have a pleasant aroma. However, the increase in production has not been accompanied by a significant increase in productivity. The expansion of chrysanthemum cultivation in Bandung Regency shows a downward trend, although there has been a slight increase lately. The potential of chrysanthemums depends on the suitability of the growing area. Based on this, it is necessary to carry out management and analysis related to the suitability of chrysanthemum cultivation land in Bandung Regency, West Java. The purpose of this study is to identify and evaluate land that is suitable for chrysanthemum cultivation in Bandung Regency. Methods: This research study was carried out using Geographic Information System (GIS) analysis with a weighted overlay method using ArcGIS Pro. Findings: Based on the results of the analysis, it was found that the area suitable for chrysanthemum cultivation is at an altitude of 0-1500 meters above sea level (masl) with a slope of 0-16%, in the soil types of Andosol and Gleisol, and with a soil surface temperature between 17-30ºC. The land suitable for chrysanthemum cultivation in Bandung Regency is approximately 40,192.23 hectares or around 23.03% of the area of Bandung Regency. less than the area that is classified as